The Role of Bhabinkamtibmas in Counseling Through the Friday Confidential Program to Prevent Theft in the Jurisdiction of Blitar Police - Sitio, Geri Dave L.A (Advances in Police Science Research Journal, 2024)
This study aims to analyze two main issues: (1) The implementation of the counseling program called "Jum’at Curhat" by Bhabinkamtibmas (Police Officers assigned to community outreach). (2) The role of Bhabinkamtibmas in conducting the counseling program "Jum’at Curhat" to prevent motor vehicle theft in the jurisdiction of Polres Blitar. This research employs a qualitative approach and field research methodology to understand the implementation of the "Jum’at Curhat" counseling program by Bhabinkamtibmas in preventing motor vehicle theft. This method allows researchers to comprehend the context, process, and meaning behind the interaction between Bhabinkamtibmas and the community deeply through direct observation in the field. The research findings indicate that the "Jum’at Curhat" program by Bhabinkamtibmas aims to increase community participation in preventing motor vehicle theft. However, in practice, this program is not fully effective due to the need for active support from the community and swift action from the police. The role of Bhabinkamtibmas in providing guidance and counseling to the community, especially through the "Jum’at Curhat" program, is crucial for fostering closer relations between the police and the community and detecting potential security issues. Nevertheless, internal factors such as limited human resources, budget constraints, and inadequate facilities, as well as suboptimal community participation, pose challenges to the effectiveness of this program. To enhance the effectiveness of the "Jum’at Curhat" program and address the challenges faced, Polres Blitar needs to take strategic collaborative measures with external parties, such as local government and relevant stakeholders. Such collaboration can provide additional support in terms of human resources and can optimize the budget required to support Bhabinkamtibmas activities and expand the coverage of the "Jum’at Curhat" program. Additionally, there is a need to strengthen training and mentoring for Bhabinkamtibmas in counseling techniques, effective communication, and conflict resolution. Moreover, direct supervision by superiors is essential to help improve the abilities of Bhabinkamtibmas in executing their duties more effectively and efficiently.